Eufemisme dan Disfemisme dalam Karangan Emha Ainun Nadjib: “Hidup Itu Harus Pintar Ngegas dan Ngerem” - Habib Rois (Universitas Muhammadiyah Jember, 2021)
Changes in the meaning of words with refinement (euphemism) and refinement (dysfemism) occur at the level of a sentence marked by words, phrases and clauses. The purpose of this research is to describe the forms of euphemisms and dysphemisms in the essay of Emha Ainun Nadjib (Cak Nun) with the title